An Overview of the Dìz’tè Segmental Phonology From an Oral Text - Hernández Luna, Mario Ulises (2024)
This article explores some phonological processes of Dí’ztè, a Zapotec language spoken in the Southern Highlands and Coast regions of Oaxaca, Mexico, from an oral text. The main goal of this paper is to show that phonological analysis based on an oral text offers a greater richness of processes than the phonological analyses based on diagnostic lists or carrier phrases. The oral text Liz mbol Wel comes from the Loxicha tradition and tells us the story of an indigenous family from Piedra del Sol, a community in Santo Domingo de Morelos, who lived in a very small house. After the arrival of new family members, Don Manuel’s wife makes the request to build a bigger house. Don Manuel agrees and asks for the support of the community to build his new house. In gratitude, he offers a meal with tortillas, mole and tepache. Based on this short oral text we analyze some phonological processes of the language.